ROBUSTNESS OF PRESTRESSED REINFORCED CONCRETE STRUCTURES UNDER SPECIAL IMPACTS - Fedorova, Natalia; Iliushchenko, Tatiana (Journal of Applied Engineering Science, 2024)
The purpose of the study was to develop the principles of the theory of robustness of reinforced concrete structural systems of buildings and structures with prestressed elements and methods of protecting them from progressive collapse under special impacts. To achieve this, the article presents the results of studies of monolithic reinforced concrete frames of multi-storey buildings and reinforced concrete frames, with prestressed elements in transcendent states caused by special effects, are given in the article. The current state of the problem of robustness of building frames under special impacts is considered. A method for calculating the reinforced concrete frame of a multi-storey building with prestressed elements has been developed and its static-dynamic deformation has been studied to determine the robustness parameter. The parameters of deformation and destruction of prestressed reinforced concrete multi-story frame frames of buildings under design and beyond design impacts are experimentally determined. The results of the experimental study of frame structures are compared with the results of studies of similar structures without prestressing. The obtained results of the study can be used in the development of methods for protecting the frames of multi-storey buildings from progressive collapse.